GC-MS modified quechers method for multiresidue pesticide determination in red wine - Pelajić, Maja (Array, 2019)
This work reports a new selective and accurate multiresidue procedure for determination of 25 pesticides in red wine by GC-MS. Proposed procedure uses an original approach in sample preparation technique based on QuEChERS theory. Main focus of method development was modification of salts thus increasing ionic strength of solution which improved pesticides partitioning and extraction efficiency. LOQs were in the range 0.01–250 μg L–1 with 56 % of target pesticides below or equal to 10 μg L–1. RSD for most pesticides was <20 % and recoveries were in the range 70–120 %. Matrix effect was found to be high for five pesticides confirming sample preparation procedure to be efficient. The proposed procedure was applied to 12 wine samples of different variety with determination of 40 % of target pesticides. Developed GC-MS methodology provides novel, selective and accurate approach for determination of 25 pesticide residues in red wine.